Comparative Assessment of Cuspal Deflection in Premolars Restored with Bulk-Fill and Conventional Composite Resins - Ebrahim Yarmohammadi; Shahin Kasraei; Yasaman Sadeghi (Tehran University of Medical Sciences, 2020)
Objectives: It has been reported that bulk-fill composites simplify tooth restoration with no adverse effect on the success rate. This study sought to assess the cuspal deflection of premolars with mesio-occluso-distal (MOD) cavities restored with bulk-fill and conventional posterior composite resins. Materials and Methods: This in-vitro experimental study was conducted on 64 human maxillary premolars. MOD cavities were prepared on teeth and restored with Filtek P60 conventional composite and Filtek Bulk Fill flowable, X-tra fill, and X-tra base bulk-fill composites in four groups (n=16). Distance between the cusp tips was measured before, five minutes, 24 hours, 48 hours, and one week after restoration. The data were analyzed using repeated-measures analysis of variance (ANOVA) and Tukey's test (α=0.05). Results: The mean±standard deviation (SD) of cuspal deflection at five minutes after the restoration was 13.5±5.3, 12.2±3.5, 11.3±4.4, and 10.4±3.7 µm for Filtek P60, Filtek Bulk Fill, X-tra fill, and X-tra base, respectively. ANOVA showed that bulk-fill composites did not cause a significant reduction in cuspal deflection compared to P60 (P>0.05). Cuspal deflection in all groups significantly decreased with time (P<0.05). Conclusion: Bulk-fill composites have no superiority over P60 in the reduction of cuspal deflection. The cuspal deflection was variable at different time points in all groups and decreased over time.